Transovarial Infection of Dengue Virus in Aedes aegypti and Aedes albopictus - Wanti, Wanti; Isnawati, Isnawati; Respati, Titik (KEMAS: Jurnal Kesehatan Masyarakat, 2022)
Nowadays, Dengue Haemorrhagic Fever (DHF) is still a significant health problem. Including in Kupang City. The existence of transovarial infection of Dengue virus is essential to know to support the prevention to be more effective and efficient. This study aimed to determine the existence of transovarial infectious and the serotypes variability of Dengue virus in Aedes sp in Kupang City. This observational research took place in nine villages in Kupang City in 2017. Where 20 houses in each village are observed to collect Aedes sp eggs. Cluster sampling was conducted to choose houses with DHF cases and surrounding areas 100 m from the cases. Ovitrap and Ovistrip were used to collect Aedes sp eggs, then Aedes sp eggs are reared in Parasitology Laboratory UGM. Adults mosquitoes from rearing were observed the transovarial Infection and Dengue Virus Serotype by One Step RT-PCR followed by nested PCR. This research found a transovarial infection in Aedes aegypti  and Aedes albopictus   and for Denvir-2 and Denvir-3. This finding is a change from previous findings in the same place where only Denvir-1 was transmitted transovarially in Aedes sp.